Handbook of Nutraceuticals for Clinical Use - Cicero, Arrigo F.G (Springer International Publishing, 2018)
This handbook provides key information on the clinical use of nutraceuticals, an increasingly common practice grounded in an understanding of the pharmacological activities of natural compounds and clinical evidence of efficacy and safety. Each chapter examines the effects of nutraceuticals in different therapeutic contexts, including nutraceuticals active on the digestive system, heart, lipid and glucose metabolism, and immune system. The authors also address relevant concerns such as relative and absolute contraindications, range of tested doses (efficacious and safe), possible side effects and pharmacological interactions, and the scientific level of clinical evidence for each product. Despite the availability of a large number of nutraceuticals on the market, the same compound is often offered by different industries at different dosages and concentrations, with different titration and often with different suggestions of efficacy. Available academic books on nutraceuticals prioritize summarizing information or focus on the pharmacological aspects on cells or animals models rather than on proof in humans. The handbook takes a unique and practical approach intended to assist clinicians, pharmacologists, nutritionists, and dietitians considering prescribing nutraceuticals for therapeutic use. Renowned expert Professor Arrigo Cicero is known internationally for his work in nutraceuticals, and currently serves as President of the Italian Nutraceutical Society. .